Integration of Dakwah, Culture, and Economy (General and Islamic) - Idris Idris; Syaifullah MS; Sarpika Datumla (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The integration of da'wah, culture, and economics is a comprehensive approach aimed at developing society holistically through a blend of spiritual values, social identity, and material well-being. Da'wah is not only understood as the activity of conveying Islamic teachings, but also as an empowerment process that utilizes the potential of local culture as a medium for internalizing religious values. This approach enables da'wah to be received more effectively because it aligns with traditions, local wisdom, and the social structure of the community. By adapting Islamic values ​​to cultural elements, harmony is created between religious teachings and social life, strengthening character, morality, and community cohesion. In addition to cultural aspects, the integration of da'wah into the economic sphere encourages the formation of an ethical, just, and sustainable economic system. Islamic values ​​such as trustworthiness, honesty, hard work, and social solidarity serve as the foundation for developing community economic activities, including micro-enterprises, sharia cooperatives, and a culture-based creative economy. The synergy between da'wah, culture, and the economy produces a model of community development that prioritizes not only material growth but also moral nobility and the preservation of local identity. Thus, the integration of these three aspects is a crucial strategy for realizing a religious, cultured, and prosperous society in the face of global dynamics and social change.